A Fractional Order Model for HIV/AIDS With Treatment and Optimal Control Using Caputo Derivative - Abdul-Aziz Hussein; Benyam Mebrate (International Journal of Mathematics and Mathematical Sciences)
In this paper, we are concerned with a deterministic Caputo fractional derivative mathematical model of HIV/AIDS with treatment and optimal control. We formulate a mathematical model that contains six compartments (including primary infection and treatment) and show that the model is well-posed. We calculate the reproduction number and free and endemic equilibrium points. We prove the stability of free and endemic equilibrium points. The local stability is carried out by the linearization method, whereas the global stability is performed by Mittag–Leffler stability. We consider four control mechanisms and show their impact on the prevalence of HIV infection. Numerical solutions are performed using the optimal case of the two-stage explicit fractional order Runge–Kutta methods.